Mutant p53s generate pro-invasive niches by influencing exosome podocalyxin levels. Issue 1 (December 2018) - Novo, David; Heath, Nikki; Mitchell, Louise; Caligiuri, Giuseppina; MacFarlane, Amanda; Reijmer, Dide; Charlton, Laura; Knight, John; Calka, Monika; McGhee, Ewan; Dornier, Emmanuel; Sumpton, David; et al.
Abstract Mutant p53s (mutp53) increase cancer invasiveness by upregulating Rab-coupling protein (RCP) and diacylglycerol kinase-α (DGKα)-dependent endosomal recycling. Here we report that mutp53-expressing tumour cells produce exosomes that mediate intercellular transfer of mutp53's invasive/migratory gain-of-function by increasing RCP-dependent integrin recycling in other tumour cells. This process depends on mutp53's ability to control production of the sialomucin, podocalyxin, and activity of the Rab35 GTPase which interacts with podocalyxin to influence its sorting to exosomes. Exosomes from mutp53-expressing tumour cells also influence integrin trafficking in normal fibroblasts to promote deposition of a highly pro-invasive extracellular matrix (ECM), and quantitative second harmonic generation microscopy indicates that this ECM displays a characteristic orthogonal morphology. The lung ECM of mice possessing mutp53-driven pancreatic adenocarcinomas also displays increased orthogonal characteristics which precedes metastasis, indicating that mutp53 can influence the microenvironment in distant organs in a way that can support invasive growth. Some p53 mutants promote invasive migration of cancer cells and metastasis of tumours in vivo. However the key mechanistic details behind these phenomena remain unclear. Here the authors propose a non-cell autonomous mechanism involving fibroblasts, whereby mutant p53-expressing cancer cells activate an exosome-mediated mechanism that influences integrin recycling in fibroblasts, thus influencing extracellular matrix remodelling to favour cancer cell invasion and migration.